THE EFFECT OF BRAND IMAGE AND CUSTOMER RELATIONSHIP ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION AT PRIMARY SCHOOL AL-ULUM - Dian Setyorini; Satria Tirtayasa; Hazamanan Khair (SEAN Institute, 2023)
This study aims to determine the effect of brand image and customer relationship on customer loyalty mediated by customer satisfaction. The population of this study was all parents of Primary School Al-Ulum students, using the slovin formula as a sampling technique. Data analysis techniques using path analysis. The results of this study indicate that brand image has a significant effect on consumer satisfaction. Customer Relationship has a significant effect on Consumer Satisfaction. Brand Image has a significant effect on Customer Loyalty. Customer Relationship has a significant effect on Customer Loyalty at Primary School Al-Ulum. Consumer Satisfaction has a significant effect on Customer Loyalty at Primary School Al-Ulum. Consumer Satisfaction can mediate the effect of Brand Image on Customer Loyalty. Consumer Satisfaction can mediate the influence of Customer Relationships on Customer Loyalty.